2003
DOI: 10.1002/art.11209
|View full text |Cite
|
Sign up to set email alerts
|

The combination of insulin‐like growth factor 1 and osteogenic protein 1 promotes increased survival of and matrix synthesis by normal and osteoarthritic human articular chondrocytes

Abstract: Objective. Although growth factor therapy could be an attractive method for stimulating the repair of damaged cartilage matrix, there is evidence that with aging and/or with the development of osteoarthritis (OA), articular chondrocytes may become unresponsive to growth factor stimulation. The aim of the current study was to compare the ability of insulin-like growth factor 1 (IGF-1) and osteogenic protein 1 (OP-1), alone and in combination, to stimulate human normal and OA chondrocytes in culture.Methods. Cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 129 publications
9
142
2
1
Order By: Relevance
“…After 26 days, the amounts of proteoglycans significantly increased in the treated chondrocytes (1.73-fold in normal [P ϭ 0.029] and 1.70-fold in OA [P Ͻ 0.001] chondrocytes), whereas they remained unchanged in the control chondrocytes (P ϭ 0.939 for normal and P ϭ 0.912 for OA chondrocytes). OA chondrocytes always contained less proteoglycans than the normal counterparts, as has previously been reported (38). Notably, the contents were significantly higher in treated OA chondrocytes than in control normal chondrocytes (1.62-fold; P Ͻ 0.001).…”
Section: Expression Of a Sox9 Gene Cassette In Human Articular Chondrsupporting
confidence: 81%
“…After 26 days, the amounts of proteoglycans significantly increased in the treated chondrocytes (1.73-fold in normal [P ϭ 0.029] and 1.70-fold in OA [P Ͻ 0.001] chondrocytes), whereas they remained unchanged in the control chondrocytes (P ϭ 0.939 for normal and P ϭ 0.912 for OA chondrocytes). OA chondrocytes always contained less proteoglycans than the normal counterparts, as has previously been reported (38). Notably, the contents were significantly higher in treated OA chondrocytes than in control normal chondrocytes (1.62-fold; P Ͻ 0.001).…”
Section: Expression Of a Sox9 Gene Cassette In Human Articular Chondrsupporting
confidence: 81%
“…Working synergistically, these biologically active proteins stimulate the proliferation and differentiation of fibroblasts, osteoblasts, chondrocytes, and mesenchymal stem cells [30].…”
Section: Resultsmentioning
confidence: 99%
“…And special attention has also been paid to IGF-1 as a factor involved in cartilage repair. In this direction, studies have reported that in human cartilage cell culture [32] and in cultured articular chondrocytes from different animals [33][34][35], the combined use of the three growth factors significantly increased proteoglycans synthesis. However, mitogenic activity was similar to cultures in which the medium contained bovine fetal serum alone [35].…”
Section: Discussionmentioning
confidence: 99%